RADIOGRAPHIC ASSESSMENT OF SPINO-PELVIC ALIGNMENT OF INDIAN YOUNG AND ELDERLY POPULATION IN COMMON INDIAN SITTING POSTURES AND STANDING: INFLUENCE OF AGE IN THE DIFFERENCE BETWEEN THESE POSITIONS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Restoring the sagittal spino-pelvic alignment is the key factor in attaining the desirable functional outcomes after spinal deformity correction and degenerative spine surgeries. The existing concepts of sagittal balance are in most cases based on standing radiographic parameters. Though, the Indian population, mainly the one living in rural areas, frequently adopts functional postures like cross-legged sitting and squatting as part of daily life. The impact of these postures and age-related differences on sagittal spino-pelvic alignment has yet to be fully explored. Objective: To analyze the radiographic alterations in spino-pelvic alignment in standing, erect sitting, cross-legged sitting, and squatting positions in young and elderly Indian populations, and to determine the role of age in these positional changes. Materials and Methods: In this prospective cross-sectional study we decided to recruit 30 healthy volunteers who were randomly subdivided into 2 groups i.e. young (age is less than 45 years) and elderly (age is more than 45 years) for the convenience of study. Saxual X-rays of lumbosacral spine with both hip joints were taken in standing, erect sitting, cross-legged sitting and squatting positions. Different sagittal spino-pelvic parameters which include Lumbar Lordosis Angle (LLA), Lumbo-sacral Angle (LSA), Sacral Slope (SS), Pelvic Tilt (PT), and Pelvic Incidence (PI) were statistically analyzed and contrasted between different postures and age groups. Statistical tests used were independent sample t-test and multifactor regression analysis, with a significance level of p < 0.05. Results: Sagittal spino-pelvic alignment changed differently and remarkably in different functional postures. On average, lumbar lordosis angle reduced gradually from 45.2 in standing posture to 10.8 in squatting posture, Though pelvic tilt increased from 15.8 to 39.4. Versus erect sitting, cross-legged sitting and squatting resulted in a more noticeable drop in lumbar lordosis and sacral slope. In standing posture, elderly ones had A lot lower lumbar lordosis and sacral slope but higher pelvic tilt versus younger ones. The younger people had a Much greater dynamic postural adaptation as the average change in lumbar lordosis between standing and squatting was 39.1 in young subjects against 27.4 in old subjects (p < 0.001). Age was negatively connected to pelvic mobility and compensatory sagittal adjustment. Conclusion: There are marked differences between the sagittal spino-pelvic alignments in standing posture and Indian sitting postures that are widely practiced. The extent of these variations is largely determined by the degree of flexibility of lumbopelvic region which tends to decrease with age. Apart from standing alignment, if functional sitting postures are also taken into account, it will lead to a deeper insight into physiological sagittal balance. In addition, it will be very helpful for surgical planning and restoring sagittal alignment in the Indian population.